Microwaves in organic synthesis - Hoz, Antonio de la (Wiley-VCH, 2012)
Includes bibliographical references and index; Volume 1. 1. Microwaves-materials interactions and dielectric properties: from molecules and macromolecules to solids and colloidal suspensions -- 2. Development and design of reactors in microwave-assisted chemistry -- 3. Key ingredients for mastery of chemical microwave processes -- 4. Nonthermal effects of microwaves in organic synthesis -- 5. Selectivity modifications under microwave irradiation -- 6. Elucidation of microwave effects: methods, theories, and predictive models -- 7. Microwave susceptors -- 8. Tools for monitoring reactions performed using microwave heating -- 9. Microwave frequency effects in organic synthesis -- 10. Organic synthesis using microwaves and supported reagents -- 11. Gaseoux reactants in microwave-assisted synthesis -- 12. Microwaves and electrochemistry -- 13. The combined use of microwaves and ultrasound: methods and practice -- 14. Microwaves in photochemistry and photocatalysis